(3GdcGTa aj CSeGA GdQLGds - (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s ((3YeQ Hf YHO GdYRjR Hf YHO Gddg GdbQTi GdaGQbi s)
(3ChdgG (B:s
(3GdMeO ddg hGdTcQ ddg hHYO agPG eNJUQ fGaY ai QLGd GdcJH GdSJI GdUMjMjf hGdSff GdCQHYI ebJVH ef JgPjH GdceGd s
(3BNQgG (B:s
(3bGdJ (B: (3CHj SGFQ CRhGL GdfHi Udi Gddg Ydgj hSde C, jONd Ydjgf CMO HQVGYI GdcHjQ JeJ cJGH GdcGTa hGdMeO ddg s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B289s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B57 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B45 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1368s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs